Hexagon in Triangle

Geometry Level 5

Six cevians are drawn as shown in figure above. These cevians form a hexagon in the middle of triangle. Cevians are such that

B A 1 B C = C B 1 C A = A C 1 A B = p \hspace{100pt}\displaystyle\frac{BA_1}{BC} = \frac{CB_1}{CA} = \frac{AC_1}{AB}=p

B A 2 B C = C B 2 C A = A C 2 A B = q \hspace{100pt}\displaystyle\frac{BA_2}{BC} = \frac{CB_2}{CA} = \frac{AC_2}{AB} = q\hspace{30pt} with 0 < p < q < 1 \hspace{30pt}\displaystyle 0 < p < q < 1

If for p = 0.1 \displaystyle p = 0.1 and some q , q\,,

area of hexagon area of A B C = 0.7 \hspace{100pt}\displaystyle\frac{\text{area of hexagon}}{\text{area of }\triangle ABC} = 0.7

Find q q and submit 100000 q \lceil 100000q \rceil


The answer is 97429.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Jun 7, 2020

This question is most easily handled using trilinear coordinates. The triangle vertices A , B , C A,B,C have coordinates A : 1 : 0 : 0 B : 0 : 1 : 0 C : 0 : 0 : 1 A:\hspace{0.3cm} 1\,:\,0\,:\,0 \hspace{2cm} B:\hspace{0.3cm} 0\,:\,1\,:\,0 \hspace{2cm} C:\hspace{0.3cm} 0\,:\,0\,:\,1 while the points A p , A q . B p , B q , C p , C q A_p,A_q.B_p,B_q,C_p,C_q where B A p = p B C BA_p =p\,BC and B A q = q B C BA_q = q\,BC (and similarly for the other four points) have coordinates A p : 0 : ( 1 p ) c : p b B p : p c : 0 : ( 1 p ) a C p : ( 1 p ) b : p a : 0 A q : 0 : ( 1 q ) c : q b B q : q c : 0 : ( 1 q ) a C q : ( 1 q ) b : q a : 0 \begin{array}{rlcrlcrl} A_p: & 0\,:\, (1-p)c\,:\, pb & \hspace{2cm} & B_p: & pc \,:\, 0\,:\, (1-p)a & \hspace{2cm}& C_p: & (1-p)b\,:\, pa\,:\, 0 \\ A_q: & 0\,:\, (1-q)c\,:\, qb && B_q: & qc \,:\, 0\,:\, (1-q)a && C_q: & (1-q)b\,:\, qa\,:\, 0 \end{array} The points A 1 , p , A 1 , q , B 1 , p , B 1 , q , C 1 , p , C 1 , q A_{1,p},A_{1,q},B_{1,p},B_{1,q},C_{1,p},C_{1,q} can now be calculated. A 1 , p A_{1,p} is the intersection of B B p BB_p and C C p CC_p , while A 1 , q A_{1,q} is the intersection of B B q BB_q and C C q CC_q , with the other four points similarly defined. Solving the trilinear equations for the intersection of these lines, we obtain the coordinates A 1 , p : p ( 1 p ) b c : p 2 a c : ( 1 p ) 2 a b A 1 , q : q ( 1 q ) b c : q 2 a c : ( 1 q ) 2 a B 1 , p : ( 1 p ) 2 b c : p ( 1 p ) b c : p 2 a b B 1 , q : ( 1 q ) 2 b c : q ( 1 q ) b c : q 2 a b C 1 , p : p 2 b c : ( 1 p ) 2 a c : p ( 1 p ) a b C 1 , q : q 2 b c : ( 1 q ) 2 a c : q ( 1 q ) a b \begin{array}{rlcrl} A_{1,p}: & p(1-p)bc\,:\, p^2ac\,:\, (1-p)^2ab & \hspace{2cm}& A_{1,q}: & q(1-q)bc\,:\, q^2ac\,:\, (1-q)^2a \\ B_{1,p}: & (1-p)^2bc\,:\, p(1-p)bc\,:\, p^2ab && B_{1,q}: & (1-q)^2bc\,:\, q(1-q)bc\,:\, q^2ab\\ C_{1,p}: & p^2bc\,:\, (1-p)^2ac\,:\, p(1-p)ab && C_{1,q}: & q^2bc\,:\, (1-q)^2ac\,:\, q(1-q)ab \end{array} Similarly, the points A 2 , A 3 , B 2 , B 3 , C 2 , C 3 A_2,A_3,B_2,B_3,C_2,C_3 can be determined, where A 2 A_2 is the intersection of B B p BB_p with C C q CC_q , while A 3 A_3 is the intersection of B B q BB_q with C C p CC_p (and the other four points are similarly defined). We obtain A 2 : p ( 1 q ) b c : p q a c : ( 1 p ) ( 1 q ) a b A 3 : ( 1 p ) q b c : p q a c : ( 1 p ) ( 1 q ) a b B 2 : ( 1 p ) ( 1 q ) b c : p ( 1 q ) a c : p q a b B 3 : ( 1 p ) ( 1 q ) b c : ( 1 p ) q a c : p q a b C 2 : p q b c : ( 1 p ) ( 1 q ) a c : p ( 1 q ) a b C 3 : p q b c : ( 1 p ) ( 1 q ) a c : ( 1 p ) q a b \begin{array}{rlcrl} A_2: & p(1-q)bc\,:\, pqac\,:\,(1-p)(1-q)ab & \hspace{2cm} & A_3: & (1-p)qbc\,:\, pqac\,:\,(1-p)(1-q)ab \\ B_2: & (1-p)(1-q)bc\,:\, p(1-q)ac\,:\, pqab && B_3: & (1-p)(1-q)bc\,:\, (1-p)qac\,:\,pqab \\ C_2: & pqbc\,:\, (1-p)(1-q)ac\,:\, p(1-q)ab && C_3: & pqbc\,:\, (1-p)(1-q)ac\,:\, (1-p)qab \end{array}

This construction will not result in a central hexagon unless q q is large enough. A hexagon will be formed so long as A 1 , q A_{1,q} lies inside the triangle A B A p ABA_p , B 1 , q B_{1,q} lies inside the triangle B C B p BCB_p and C 1 , q C_{1,q} lies inside the triangle C A C p CAC_p . Symmetry gives us that these three things either all occur at the same time, or none occur. Thus the critical case to consider is when A 1 , q A_{1,q} lies on the line A A p AA_p , which occurs when A 1 , q = B 3 = C 2 A_{1,q} = B_3 = C_2 . This implies that p ( 1 q ) = λ p q p(1-q) = \lambda pq , p q = λ ( 1 p ) ( 1 q ) pq = \lambda(1-p)(1-q) and ( 1 p ) ( 1 q ) = λ ( 1 p ) q (1-p)(1-q) = \lambda(1-p)q for some λ > 0 \lambda > 0 , which tells us that q = 1 p p + 1 p q \; = \; \frac{\sqrt{1-p}}{\sqrt{p} + \sqrt{1-p}} Equally well, for there to be an internal hexagon, the point A 1 , p A_{1,p} has to lie in the triangle A A q C AA_qC , the point B 1 , p B_{1,p} has to lie in the triangle B B q A BB_qA , and the point C 1 , p C_{1,p} has to lie in the triangle C C q B CC_qB . Again, these three things either all happen, or none of them happen; the critical case to consider is when A 1 , p A_{1,p} lies on A A q AA_q , which occurs when A 1 , p = B 2 = C 3 A_{1,p} = B_2 = C_3 . The condition for this is q = ( 1 p ) 2 p 2 + ( 1 p ) 2 q \; = \; \frac{(1-p)^2}{p^2 + (1-p)^2} We only have an internal hexagon when 1 p p + 1 p < q < ( 1 p ) 2 p 2 + ( 1 p ) 2 \frac{\sqrt{1-p}}{\sqrt{p}+\sqrt{1-p}} < q < \frac{(1-p)^2}{p^2 + (1-p)^2} . Note that this requires that 0 < p < 1 2 0 < p < \tfrac12 . Then the area of the internal hexagon is equal to the area of the triangle A 1 , p B 1 , p C 1 , p A_{1,p}B_{1,p}C_{1,p} minus the areas of the triangles A 1 , p B 2 C 3 A_{1,p}B_2C_3 , B 1 , p C 2 A 3 B_{1,p}C_2A_3 and C 1 , p A 2 B 3 C_{1,p}A_2B_3 . Standard formulae for the areas of triangles given by trilinear coordinates tell us that the last three triangles all have the same area, and that the area of the internal hexagon is Δ ( 1 p + p 2 ) 3 p ( 1 p ) p 2 ( 1 p ) 2 ( 1 p ) 2 p ( 1 p ) p 2 p 2 ( 1 p ) 2 p ( 1 p ) 3 Δ ( 1 p + p 2 ) ( 1 p + p q ) ( 1 q + p q ) p ( 1 p ) p 2 ( 1 p ) 2 ( 1 p ) ( 1 q ) p ( 1 q ) p q p q ( 1 p ) ( 1 q ) ( 1 p ) q \frac{\Delta}{(1 - p + p^2)^3}\left|\begin{array}{ccc} p(1-p) & p^2 & (1-p)^2 \\ (1-p)^2 & p(1-p) & p^2 \\ p^2 & (1-p)^2 & p(1-p) \end{array}\right| - \frac{3\Delta}{(1-p+p^2)(1-p+pq)(1-q+pq)}\left|\begin{array}{ccc}p(1-p) & p^2 & (1-p)^2 \\ (1-p)(1-q) & p(1-q) & pq \\ pq & (1-p)(1-q) & (1-p)q \end{array}\right| which simplifies to give 2 + 5 ( p + q ) 3 ( p 2 + 4 p q + q 2 ) + 8 p q ( p + q ) 8 p 2 q 2 ( 1 p + p q ) ( 1 q + p q ) Δ \frac{ -2 + 5(p + q) - 3(p^2 + 4pq + q^2) + 8pq(p + q) - 8p^2q^2}{(1 - p + pq)(1 - q + pq)}\Delta for 1 p p + 1 p < q < ( 1 p ) 2 p 2 + ( 1 p ) 2 \frac{\sqrt{1-p}}{\sqrt{p}+\sqrt{1-p}} < q < \frac{(1-p)^2}{p^2+(1-p)^2} , where Δ \Delta is the area of the original triangle A B C ABC .

If we consider the expression for the area of the internal hexagon with p = 0.1 p = 0.1 and for 0.9 0.9 + 0.1 = 3 4 < q < 81 82 = 0. 9 2 0. 1 2 + 0. 9 2 \frac{\sqrt{0.9}}{\sqrt{0.9} + \sqrt{0.1}} = \tfrac34 < q < \tfrac{81}{82} = \frac{0.9^2}{0.1^2+0.9^2} , we obtain, solving a quadratic equation for q q - thank you, @Atomsky Jahid ) a relative area of 0.7 0.7 for the internal hexagon when q = 720 739 q = \tfrac{720}{739} , and hence 1 0 5 q = 97429 \lceil 10^5 q \rceil = \boxed{97429} .

Great solution using trilinear coordinates. Your expression of area of hexagon in terms of p p and q q is correct. But I think condition for existence of hexagon is wrong. You said for any given p , p, q q must be such that 1 p + 1 < q < 1 \displaystyle \frac{1}{\sqrt{p} + 1} < q < 1 for the existence of hexagon. But take an example of p = 0.25 p = 0.25 and q = 0.65 q = 0.65 , hexagon is formed but this p p and q q do not satisfy your condition. I don't know how to post photos in comment otherwise I would have shown it to you. But I am giving you a link of desmos graphing calculator - https://www.desmos.com/calculator/lrrnzwoxjg . You can see there how hexagon is varying with p p and q q .

Shikhar Srivastava - 1 year ago

Log in to reply

You are right. I have corrected the critical value for q q to its actual value of 1 p p + 1 p \frac{\sqrt{1-p}}{\sqrt{p} + \sqrt{1-p}} . The following pictures show what happens either side of the critical value for p = 0.25 p = 0.25 .

Mark Hennings - 1 year ago

Log in to reply

There is also an upper bound on q in terms of p. Try to find out.

Shikhar Srivastava - 1 year ago

Log in to reply

@Shikhar Srivastava Fixed that one, too. Of course, we need all six "little" triangles in order to have a hexagon.

Mark Hennings - 1 year ago

Log in to reply

@Mark Hennings Yaah! Now that's correct. Well your approach of using trilinear coordinates is good. I have used only elementary geometry which was quite time taking.

Shikhar Srivastava - 1 year ago

Log in to reply

@Shikhar Srivastava It is worth noting that one implication of the inequality giving the valid range of q q is that p < 1 2 p < \tfrac12 .

Mark Hennings - 1 year ago

Log in to reply

@Mark Hennings Yes, and if we remove the constraint p < q p < q then we see that for any given p p value of should be in between 1 p 1 p + p \displaystyle \frac{\sqrt{1-p}}{\sqrt{1-p} + \sqrt{p}} and ( 1 p ) 2 ( 1 p ) 2 + p 2 \displaystyle\frac{(1-p)^2}{(1-p)^2 + p^2} . First expression is the lower bound of q q when p < 1 2 p < \frac{1}{2} and upper bound of q q when p > 1 2 p > \frac{1}{2} . Similarly the second expression is upper bound when p < 1 2 p < \frac{1}{2} and lower bound when p > 1 2 p > \frac{1}{2} . This is described in the figure below.

In the graph x axis is p p , y-axis is q q and curves are the limit. We also infer that p p and q q cannot be both less than 1 2 \frac{1}{2} and cannot be both greater than 1 2 \frac{1}{2} .

Shikhar Srivastava - 1 year ago

The only way I know to post a picture in a comment is to open up one of your own solutions, post a picture there, copy the resulting hyperlink, get out of your own solution, and paste the hyperlink into the comment!

Mark Hennings - 1 year ago

Log in to reply

Oh! Thats the good way . Thanks for telling.

Shikhar Srivastava - 1 year ago

There exists an analytical method for finding out q q . The value of q q is 720 739 \frac{720}{739} .

Atomsky Jahid - 1 year ago

Log in to reply

Of course, since the necessary equation is simply a quadratic in q q , and we can ignore the second solution of q = 1 q=1 .

Mark Hennings - 1 year ago
Atomsky Jahid
Jun 9, 2020

This problem is extremely suitable for the use of Routh's theorem . Routh's theorem Routh's theorem

The ratio of the area of a cevian triangle to the original triangle depicted above is ( x y z 1 ) 2 ( x y + y + 1 ) ( y z + z + 1 ) ( z x + x + 1 ) \frac{(xyz-1)^2}{(xy+y+1)(yz+z+1)(zx+x+1)}

Now, let's go back to the triangle of our problem. We will first find the area of the red triangle and then subtract the areas of of the smaller triangles around its vertices to get the area of the hexagon. It should be noted that the three smaller triangles whose areas are to be subtracted have equal areas. Our problem Our problem

Here, B A 1 B C = 1 10 \frac{BA_{1}}{BC} = \frac{1}{10} A 1 C B A 1 = 9 \implies \frac{A_{1}C}{BA_{1}} = 9

Let's assume A 2 C B A 2 = x \frac{A_{2}C}{BA_{2}} = x B A 2 B C = q = 1 1 + x \implies \frac{BA_{2}}{BC} = q = \frac{1}{1+x}

Now, we get the following equation. ( 9 3 1 ) 2 ( 9 2 + 9 + 1 ) 3 3 ( 81 x 1 ) 2 ( 9 x + 10 ) ( 81 + 10 ) ( 10 x + 1 ) = 7 10 \frac{(9^3-1)^2}{(9^2+9+1)^3} - \frac{3(81x-1)^2}{(9x+10)(81+10)(10x+1)} = \frac{7}{10} This simplifies to x = 19 720 x = \frac{19}{720}

Therefore, q = 1 1 + x = 720 739 q = \frac{1}{1+x} = \frac{720}{739}

Nice solution.You genius

Madhurja Sarker - 1 year ago

Brilliant Solution. Short and simple.

Shikhar Srivastava - 1 year ago

Just to make it easy.

Niranjan Khanderia - 1 year ago
David Vreken
Jun 9, 2020

The triangle can be stretched and skewed to an equilateral triangle with unit sides and still preserve the ratio of areas. Placing B B at the origin and C C at ( 1 , 0 ) (1, 0) , then A A is ( 1 2 , 3 2 ) (\frac{1}{2}, \frac{\sqrt{3}}{2}) , O O is ( 1 2 , 3 6 ) (\frac{1}{2}, \frac{\sqrt{3}}{6}) , A 1 A_1 is ( 1 10 , 0 ) (\frac{1}{10}, 0) , A 2 A_2 is ( q , 0 ) (q, 0) , B 1 B_1 is ( 19 20 , 3 20 ) (\frac{19}{20}, \frac{\sqrt{3}}{20}) , C 1 C_1 is ( 9 20 , 9 3 20 ) (\frac{9}{20}, \frac{9\sqrt{3}}{20}) , and C 2 C_2 is ( 1 2 ( 1 q ) , 3 2 ( 1 q ) ) (\frac{1}{2}(1 - q), \frac{\sqrt{3}}{2}(1 - q)) .

The equation of the line B B 1 BB_1 is y = 3 2 x y = \frac{\sqrt{3}}{2}x , the line C C 2 CC_2 is y = 3 ( q 1 ) q + 1 ( x 1 ) y = \frac{\sqrt{3}(q - 1)}{q + 1}(x - 1) , the line A A 1 AA_1 is y = 5 3 4 ( x 1 10 ) y = \frac{5\sqrt{3}}{4}(x - \frac{1}{10}) , and the line A A 2 AA_2 is y = 3 1 2 q ( x q ) y = \frac{\sqrt{3}}{1 - 2q}(x - q) .

A A 1 AA_1 and C C 1 CC_1 intersect at D ( 9 7 q 2 q + 18 , 9 3 9 3 q 2 q + 18 ) D(\frac{9 - 7q}{2q + 18}, \frac{9\sqrt{3} - 9\sqrt{3}q}{2q + 18}) , A A 1 AA_1 and B B 1 BB_1 intersect at E ( 19 q 19 18 q 20 , 3 q 3 18 q 20 ) E(\frac{19q - 19}{18q - 20}, \frac{\sqrt{3}q - \sqrt{3}}{18q - 20}) , and A A 2 AA_2 and B B 1 BB_1 intersect at F ( 19 q 2 q + 18 , 3 q 2 q + 18 ) F(\frac{19q}{2q + 18}, \frac{\sqrt{3}q}{2q + 18}) .

The area of D O E \triangle DOE is A D O E = 1 2 ( ( D x O x ) ( E y O y ) ( E x O x ) ( D y O y ) ) = 164 3 q 2 244 3 q + 81 3 108 q 2 + 852 q 1080 A_{\triangle DOE} = \frac{1}{2}((D_x - O_x)(E_y - O_y) - (E_x - O_x)(D_y - O_y)) = \frac{164\sqrt{3}q^2 - 244\sqrt{3}q + 81\sqrt{3}}{108q^2 + 852q - 1080} and the area of E O F \triangle EOF is A D O E = 1 2 ( ( E x O x ) ( F y O y ) ( F x O x ) ( E y O y ) ) = 16 3 q 2 36 3 q + 18 3 27 q 2 + 213 q 270 A_{\triangle DOE} = \frac{1}{2}((E_x - O_x)(F_y - O_y) - (F_x - O_x)(E_y - O_y)) = \frac{16\sqrt{3}q^2 - 36\sqrt{3}q + 18\sqrt{3}}{27q^2 + 213q - 270} .

The area of A B C \triangle ABC is A A B C = 3 4 A_{\triangle ABC} = \frac{\sqrt{3}}{4} and by symmetry the area of the hexagon is 3 ( A D O E + A E O F ) 3(A_{\triangle DOE} + A_{\triangle EOF}) , and since area of hexagon area of △ABC = 0.7 \frac{\text{area of hexagon}}{\text{area of △ABC}} = 0.7 , we have 3 ( 164 3 q 2 244 3 q + 81 3 108 q 2 + 852 q 1080 + 16 3 q 2 36 3 q + 18 3 27 q 2 + 213 q 270 ) 3 4 = 7 10 \frac{3(\frac{164\sqrt{3}q^2 - 244\sqrt{3}q + 81\sqrt{3}}{108q^2 + 852q - 1080} + \frac{16\sqrt{3}q^2 - 36\sqrt{3}q + 18\sqrt{3}}{27q^2 + 213q - 270})}{\frac{\sqrt{3}}{4}} = \frac{7}{10} , which rearranges to 739 q 2 1459 q + 720 = 0 739q^2 - 1459q + 720 = 0 and solves to q = 720 739 q = \frac{720}{739} for q < 1 q < 1 .

Therefore, 100000 q = 100000 720 739 = 97429 \lceil 100000q \rceil = \lceil 100000 \cdot \frac{720}{739} \rceil = \boxed{97429} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...